2021
DOI: 10.1186/s13613-020-00799-w
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound score predicts outcomes in COVID-19 patients admitted to the emergency department

Abstract: Background During the COVID-19 pandemic, creating tools to assess disease severity is one of the most important aspects of reducing the burden on emergency departments. Lung ultrasound has a high accuracy for the diagnosis of pulmonary diseases; however, there are few prospective studies demonstrating that lung ultrasound can predict outcomes in COVID-19 patients. We hypothesized that lung ultrasound score (LUS) at hospital admission could predict outcomes of COVID-19 patients. This is a prospe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
2
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 23 publications
7
93
2
6
Order By: Relevance
“…This is surprising because several studies have shown that changes in these parameters are associated with higher severity of illness [ 13 15 ]. Other studies demonstrated that higher LU scores are associated with an increased disease severity [ 11 , 16 , 17 ]. The lack of relation might be explained by the differences in the studied cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising because several studies have shown that changes in these parameters are associated with higher severity of illness [ 13 15 ]. Other studies demonstrated that higher LU scores are associated with an increased disease severity [ 11 , 16 , 17 ]. The lack of relation might be explained by the differences in the studied cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, lung ultrasound was able to detect COVID-19 patients who would benefit from tracheal intubation. 115 Another score to predict failure of non-invasive respiratory strategies has been developed 116 and externally validated. The score includes age, number of comorbidities, respiratory rate-oxygenation index (ROX), GCS, and use of vasopressors on the first day of non-invasive respiratory support as independent predictors of failure.…”
Section: How Can P-sili Be Prevented?mentioning
confidence: 99%
“…Several studies investigated the prognostic value of ultrasound findings in patients with COVID-19 pneumonia; however, most of them were carried out in patients admitted to hospitals and, therefore, in a more advanced stage of the disease [ 11 , 12 , 13 , 14 , 15 , 16 ]. Many of these studies used pleural abnormalities or the presence of condensations to categorize the risk of deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the scientific community has accepted that LUS is a first-line tool in the early diagnosis of COVID-19 pneumonia [ 10 ]. Some studies assessed the ability of LUS to predict the evolution of the patient [ 11 , 12 , 13 , 14 , 15 , 16 ], however, most of them were carried out in hospital settings; therefore, they did not consider situations prior to hospital admission. Few studies addressed the use of LUS in primary health care (PHC) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%